Using intelligent-system metods in mechanical engineering to predict the topographical property of materials with the topological property of visibility graphs in a 3D space - Babič, Matej (Elektrotehniški vestnik, 2015)
Intelligent systems are a new wave of the embedded and real-time systems that are highly connected, with a massive processing power and performing complex applications. Their pervasiveness is reshaping the real world and teh way, we interact with our digital life. These intelligent systems are creating new opportunities for industry and business, and new experiences for users and consumers. They can be found in all domains: automotive, rail, aerospace, defence, energy, healthcare, telecoms and consumer electronics. In this paper we use an intelligent system method to predict the roughness of hardened specimens. We use an algorithm for the construction visibility graphs in a 3D space to analyse topographical properties of hardened specimens. Drawing graphs as nodes connected by links in 3D space is visually compelling but computationally difficult. Thus, the construction of the 3D visibility graphs is highly complex and requires in their professional computers or supercomputers. The microstructure of the robot-laser-hardened specimens is very complex; however, we can present it using 3D visibility graphs. For predicting the surface roughness of the hardened specimens we use the neural network, genetic algorithm and multiple regression. Using the intelligent systems we increase production of the laser-hardening process by decreasing the time process and increasing the topographical property of materials.
Keywords: inteligentni sistemi; topografija; topography; materiali; gensko programiranje; kompleksna geometrija